Hydrological responses of a watershed to historical land use evolution and future land use scenarios under climate change conditions - Quilbé, R.; Rousseau, A. N.; Moquet, J.-S.; Savary, S.; Ricard, S.; Garbouj, M. S. (Hydrology and Earth System Sciences, 2008)
Watershed runoff is closely related to land use but this influence is difficult to quantify. This study focused on the Chaudière River watershed (Québec,...
Publisher: Copernicus Publications
Keywords: Ouvrage_Collectif_Numéro1; Rousseau_Alain